Tanggung Jawab Perbankan Terhadap Hak Karyawan: Perspektif Hukum Perbankan dan Ketenagakerjaan di Indonesia - Dalimunthe, Nikmah; Aramita, Aramita (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the banking responsibility towards employee rights in Indonesia from the perspective of banking and employment law. With a qualitative approach and normative legal research methods, this study examines the regulations governing the employment relationship between banks and employees, including Law No. 13 of 2003 concerning Employment and related regulations in the banking sector. The data used are in the form of relevant legal documents, journals, articles, and reports, which are collected through literature studies and case analysis. The analysis is carried out descriptively-analytically to see the application of the law in practice and the challenges faced in fulfilling employee rights in the banking sector. The results of the study indicate that although there are regulations governing employee rights, inconsistent implementation, especially for contract or outsourcing workers, often results in gaps in the fulfillment of these rights. In addition, business ethics in banking plays an important role in ensuring fairer protection of employee rights. This study also identifies challenges in the application of the law that can be detrimental to employee welfare and overall organizational performance.